Immune Effector Recovery in Chronic Myeloid Leukemia and Treatment-Free Remission - Hughes, Amy; Yong, Agnes S. M. (Frontiers in Immunology, 2017)
Chronic Myeloid Leukaemia (CML) is a haematological cancer, characterised by a reciprocal chromosomal translocation between chromosomes 9 and 22 (t(9;22)), producing the Bcr-Abl oncogene. Tyrosine kinase inhibitors (TKI) represent the standard of care for CML patients and exert a dual mode of action; direct oncokinase inhibition and restoration of effector-mediated immune surveillance, which is rendered dysfunctional in CML patients at diagnosis, prior to TKI therapy. TKIs such as imatinib, and more potent second-generation nilotinib and dasatinib induce a high rate of deep molecular response (DMR, BCR-ABL1 ≤0.01%) in CML patients. As a result, the more recent goal of therapy in CML treatment is to induce a durable DMR as a prelude to successful treatment free remission (TFR), which occurs in approximately half of all CML patients who cease TKI therapy. The lack of overt relapse in such patients has been attributed to immunological control of CML. In this review, we discuss an immunological timeline to successful TFR, focusing on the immunology of CML during TKI treatment; an initial period of immune suppression, limiting anti-tumour immune effector responses in newly diagnosed CML patients, linked to an expansion of immature Myeloid Derived Suppressor Cells and Regulatory T cells and aberrant expression of immune checkpoint signaling pathways, including programmed death-1 (PD-1)/PD-L1. Commencement of TKI treatment is associated with immune system re-activation and restoration of effector-mediated (Natural Killer cell and T cell) immune surveillance in CML patients, albeit with differing frequencies in concert with differing levels of molecular response achieved on TKI. DMR is associated with maximal restoration of immune recovery in CML patients on TKI. Current data suggests a net balance between both the effector and suppressor arms of the immune system, at a minimum involving mature, cytotoxic CD56dim NK cells may be important in mediating TFR success. However, a major goal remains in CML to identify the most effective pathways to target to maximize an advantageous immune response and promote TFR success.